LncRNA CASC11 aggravates diabetic nephropathy via targeting FoxO1: CASC11 aggravates diabetic nephropathy - Zhang, Yun; Shi, Shuhan; Lin, Changda; Che, Lishuang; Li, Yuangen; Zeng, Quanzuan; Lin, Weiyuan (Journal of Medical Biochemistry, 2023)
Background: To explore the biological effects of CASC11 on aggravating diabetic nephropathy (DN) by regulating FoxO1 (forkhead transcription factor O1). Methods: Serum levels of CASC11 and FoxO1 in DN patients were detected. The possibility of CASC11 in predicting the onset of DN was analyzed by depicting ROC curves. Correlation between CASC11 and FoxO1 was evaluated by Pearson correlation test. After intervening CASC11 and FoxO1 levels, changes in proliferative and migratory abilities in HG-induced kidney mesangial cells were determinedrespectively. Expression levels of TGF-β1 and Smads regulated by both CASC11 and FoxO1 were examined by Western blot. Results: CASC11 was highly expressed in serum of DN patients, whereas FoxO1 was downregulated, showing a negative correlation. CASC11 may be a diagnostic marker for DN. It attenuated proliferative and migratory abilities in HG-induced kidney mesangial cells, and the inhibitory effects of CASC11 could be abolished by overexpression of FoxO1. Protein levels of TGF-β1 and Smads were positively regulated by CASC11, which were reversed by Smads regulation. Conclusions: Through activating the TGF-β1/Smads signaling, CASC11 inhibits FoxO1 expression and thus induces the aggravation of DN.